External transluminal drainage of the pancreatic duct due to fistula caused by postbioptic pancreatic necrosis - Ignjatović Dragan; Kronja Goran; Mišović Sidor; Mirković Dragan (Vojnosanitetski Pregled)
Background. Pancreatic fistulas are not frequent after the needle biopsy of the pancreatic head. The aim was to present a patient with this type of fistula who was managed using the surgical method never previously applied in our surgical practice. Case report. In our patient, pancreatic fistula appeared at the site of the needle biopsies due to the development of the necrosis. Since the conservative treatment with octreotide and the total parenteral nutrition were without result, we turned to the surgical treatment by placing a silicone prosthesis along the pancreatic duct into the duodenum, next through the Roux-en-Y flexure to provide the external drainage of a pancreatic juice. Postoperatively, applying the conservative treatment, pancreatic fistula disappeared, and a silicone prosthesis was removed three weeks later. Conclusion. The described surgical procedure can be successful in managing fistulas which occur after the pancreatic necrosis.